Practical plant identification : including a key to native and cultivated flowering plants in north temperate regions - Cullen, J. (James) (Cambridge University Press, 2006)
Building on the success of Cullen's The Identification of Flowering Plant Families, this is an essential guide to identifying flowering plant families (wild or cultivated) in the northern hemisphere. Details of plant structure and terminology accompany practical keys to the identification of 318 of the flowering plant families.